(untitled) (Swiss Medical Weekly, 2017)
INTRODUCTION In Switzerland, the first implantation of a subcutaneous implantable cardioverter-defibrillator (S-ICD) took place in November 2012. Up until the end of 2016, a total of 111 S-ICDs have been implanted. The aim of this study was to summarise the experience of a tertiary centre in Switzerland and to discuss the results in the context of international registries. METHODS All patients in whom an S-ICD was implanted between November 2012 and the end of December 2016 at the University Heart Centre Zurich were included in this study. The clinical records of all patients were reviewed for retrospective collection of baseline characteristics as well as implantation and follow-up data. RESULTS A total of 37 S-ICDs were implanted. The majority of patients (81%) were male, the mean age was 47 ± 15 years. The most common underlying cardiac condition was coronary artery disease (30%), followed by hypertrophic cardiomyopathy (24%), inherited channelopathies (19%) and nonischaemic cardiomyopathy (11%). The median left ventricular ejection fraction was 44% (interquartile range 28–61%). There were four peri-interventional complications, all of which were pocket site-related. There were no cases of systemic infection or perioperative death. During a median follow up of 3.7 months, there were three appropriate and successful ICD shocks (8.1%). Two patients (5.4%) experienced a total of three inappropriate shocks, all due to T-wave oversensing. CONCLUSION This first large Swiss experience demonstrates results consistent with available international data. The S-ICD may hence represent an attractive alternative to conventional transvenous ICDs for a variety of patients.